Effects of spraying selenium at different stages on nutrient absorption and fruit quality of ‘Bendizao’ citrus - WEN Mingxia; WANG Peng; WU Shaohui; HUANG Bei (浙江大学学报. 农业与生命科学版)
The effects of spraying selenium (Se) at different stages on Se contents and fruit quality of citrus were studied to provide basic data for rational Se application. A foliar spray of 200 mg/L sodium selenite solution was applied to 15 years’ ‘Bendizao’ mandarin (Citrus succosa Hort. Ex Tanaka) at the young fruit stage, fruit expansion stage and fruit coloring stage, respectively. Leaf and fruit samples were collected at the maturing stage to detect Se contents, organic degree of Se, other nutrient contents and fruit quality. The result showed that spraying Se before the fruit coloring stage increased total Se contents in the leaves and fruits. Se organic proportion of fruit decreased with the delay of Se spraying date. The activities of superoxide dismutase and peroxidase under the spraying Se treatments were higher, but the content of malondialdehyde was lower. Se promoted the absorption of total nitrogen and total potassium, but inhibited the absorption of total phosphorus, total calcium and total magnesium. The fruit peel was thinner, the content of total acid was lower, and the contents of soluble solid, total sugar and vitamin C were higher by spraying Se at the young fruit stage. In conclusion, foliar spraying Se can improve the fruit quality by increasing the Se contents and affecting the balance of nutrient absorption, thus improving the antioxidant capacity and the quality of citrus fruits. The comprehensive effect of foliar spraying Se at the fruit young stage is the best.